The sub 2-h official marathon is possible: Developing a drafting strategy for a historic breakthrough in sports - Fernandes, G. D.; Gandur, N. L.; Santos, D.; Maldonado, V. (Sports Medicine - Open, 2025)
Background Drafting for drag reduction is a tactic commonly employed by elite athletes of various sports. The strategy has been adopted by Kenyan runner Eliud Kipchoge on numerous marathon events in the past, including the 2018 and 2022 editions of the Berlin marathon (where Kipchoge set two official world records), as well as in two special attempts to break the 2 h mark for the distance, the Nike Breaking2 (2017) and the INEOS 1:59 Challenge (2019), where Kipchoge used an improved drafting formation to finish in 1:59:40, although that is not recognized as an official record.